Síntese e caracterização da perovskita BaCe0,2Zr0,7Y0,1O3- δ para uso como eletólito sólido em células a combustível usando aditivos de sinterização e obtidas por método pechini modificado e reação no estado sólido - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Greenhouse gas emissions have led to significant mobilization by the community seeking sustainable alternatives for global energy supply. One such alternative is the development of fuel cells, which convert chemical energy into electrical energy, generating heat and water vapor as byproducts. Solid oxide fuel cells, especially those operating via proton transport, have gained prominence due to their ability to function at intermediate temperatures while maintaining good performance and efficiency. The construction of the electrolyte (a key component of the cell) poses a challenge; however, some formulations show promise, such as BaCe0,2Zr0,7Y0,1O3-δ (BCZY27) with the addition of sintering additives. ZnO is the most studied sintering additive in perovskite compositions, but other additives, like Fe2O3 and Mn2O3, offer advantages, although they are not widely studied for BCZY27 compositions in the literature. This study aims to analyze the BCZY27 formulation with ZnO, Fe2O3 and Mn2O3 additives synthesized using the Modified Pechini method and ZnO, Fe2O3 additives synthesized via solid-state reaction. After synthesizing the powders using both methods and sintering at 1500°C, the samples were characterized by X-ray diffraction (XRD) with Rietveld analysis, scanning electron microscopy with energy-dispersive spectroscopy (SEM-EDS), apparent density and porosity measurements, and impedance spectroscopy. Results showed effective densification (above 95%) for compositions obtained via the Modified Pechini method, regardless of the sintering additive, where densification occurred via liquid-phase sintering. In contrast, solid-state reaction- derived powders exhibited insufficient densification. Analyses revealed that Fe2O3 and Mn2O3 additives led to the formation of secondary phases during sintering, reducing conductivity and increasing activation energy compared to compositions with ZnO. Using ZnO as an additive in the solid-state reaction composition resulted in a secondary phase; however, density, activation energy, and conductivity values were within the ideal range for use as an electrolyte. The most promising result was found for the Modified Pechini composition with ZnO, which achieved approximately 98% densification, an activation energy of 0.47 eV, and a conductivity of 1.07∙10−3 S/cm, with no secondary phase formation, suggesting zinc was incorporated into the perovskite structure.
Keywords: célula a combustível; eletrólito; perovskita; aditivos de sinterização; fuel cell; electrolyte; perovskite; sintering additives; Engenharia de Materiais